Depletion-induced colloidal crystals at a wall characterised by small-angle X-ray diffraction - Xian, X; Petukhov, A; Snel, MME; Dolbnya, I; Aarts, D; Vroege, G; Lekkerkerker, H (2003)
Silica photonic colloidal crystals on a flat glass substrate have been grown using the depletion attraction induced by nonadsorbing polymers. The dried samples have been characterised with high-resolution synchrotron small-angle X-ray diffraction and their surface topography has been studied by atomic force microscopy. The presence of long-range ordered crystals with a thickness as large as 90 planes is demonstrated. However, on some places the films are polycrystalline and contain disordered regions.